2005
DOI: 10.1038/nbt1128
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial polyketide biosynthesis by de novo design and rearrangement of modular polyketide synthase genes

Abstract: Type I polyketide synthase (PKS) genes consist of modules approximately 3-6 kb long, which encode the structures of 2-carbon units in polyketide products. Alteration or replacement of individual PKS modules can lead to the biosynthesis of 'unnatural' natural products but existing techniques for this are time consuming. Here we describe a generic approach to the design of synthetic PKS genes where facile cassette assembly and interchange of modules and domains are facilitated by a repeated set of flanking restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
243
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(249 citation statements)
references
References 29 publications
2
243
0
4
Order By: Relevance
“…The UCS's functionality clearly demonstrated the portability of involved COM domains by the simultaneous formation of the expected di-and tripeptide products. Most recently, Menzella et al (14) reported on a very similar goal in the analogous polyketide synthases. By exploiting a compatible set of interpeptide linkers (also referred to as docking domains, the counterparts of NRPS COM domains), Menzella et al investigated the productive interaction between 154 bimodular combinations of donor and acceptor modules and found that nearly half of the combinations successfully mediated the biosynthesis of the desired triketide lactones.…”
Section: Tycb3mentioning
confidence: 79%
“…The UCS's functionality clearly demonstrated the portability of involved COM domains by the simultaneous formation of the expected di-and tripeptide products. Most recently, Menzella et al (14) reported on a very similar goal in the analogous polyketide synthases. By exploiting a compatible set of interpeptide linkers (also referred to as docking domains, the counterparts of NRPS COM domains), Menzella et al investigated the productive interaction between 154 bimodular combinations of donor and acceptor modules and found that nearly half of the combinations successfully mediated the biosynthesis of the desired triketide lactones.…”
Section: Tycb3mentioning
confidence: 79%
“…Library approaches can provide a direct route for obtaining and refining functional in vivo systems (39)(40)(41). In the field of metabolic engineering, for example, researchers have repeatedly improved natural product yields and synthesized analogs by searching collections of isozymes (42,43), mutant biosynthetic enzymes (3,44), or promoters and regulatory regions that modulate the expression levels of genes that alter pathway flux (45,46). Testing these multiple variables in the context of a pathway causes library sizes to rapidly swell (e.g., testing 100 mutants of enzyme A against 100 mutants of enzyme B is already Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All these platforms have dramatically improved their performance in recent years to cope with to the expected shortage of recombinant protein manufacturing capacity [2,3]. For instance, the modifications introduced in prokaryotic systems have made them increasingly able to produce and display complex proteins [4], or have facilitated the introduction of whole metabolic pathways [5]; similarly, yeast strains have been engineered to display nearlyhuman glycosylation profiles [6]; CHO cells have multiplied their yields, reaching g/L levels [7]; alternative animal systems as chicken eggs have arisen [8], and baculovirusbased systems have been adapted to the production of multi-subunit protein complexes [9].…”
Section: Introductionmentioning
confidence: 99%